Estudando geometria através de dobraduras - Frolini, Sibeli [UNESP] (2014)
This work aims to offer an alternative method for teaching Euclidean Geometry for Middle and High School students. This method includes: relaxation techniques, enhancement of concentration, improving motor function and academic performance of students, incorporating new elements to the formal language of Mathematics